1990
DOI: 10.1111/j.1530-0277.1990.tb00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Mediation of the Effect of Alcohol on Heart Rate

Abstract: Alcohol (0.5 g/kg bodyweight) was administered in two sessions and placebo in a third session to normal, healthy social drinkers. A control group was administered a mixer (i.e., no alcohol) for each of the three sessions. The heart rate and vagal tone index (V) response patterns were different to alcohol than to the mixer or placebo. The treatments did not differentially influence pulse transit time. The results indicated that the acute effect of a moderate dose of alcohol on the heart is parasympathetically (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…Decreases in vagal tone index of similar magnitude 5 min after smoking marijuana cigarettes have been noted previously . Although the cardiovascular effects of morphine, alcohol, nicotine, methylphenidate, and pentobarbitol were not as pronounced, all of these substances have been reported (Newlin et al 1990;Pretorius et al 1991;Wong et al 1991) to decrease vagal tone index in humans. Therefore, it is possible that withdrawal of vagal tone is a common factor in the response to abused drugs.…”
Section: Discussionmentioning
confidence: 96%
“…Decreases in vagal tone index of similar magnitude 5 min after smoking marijuana cigarettes have been noted previously . Although the cardiovascular effects of morphine, alcohol, nicotine, methylphenidate, and pentobarbitol were not as pronounced, all of these substances have been reported (Newlin et al 1990;Pretorius et al 1991;Wong et al 1991) to decrease vagal tone index in humans. Therefore, it is possible that withdrawal of vagal tone is a common factor in the response to abused drugs.…”
Section: Discussionmentioning
confidence: 96%
“…However, Kirschbaum et al (1993) demonstrated that HR was back to baseline levels 15 min after stress exposition, which is much shorter than what it took until our baseline started. However, the observed alcohol stimulated baseline HR increase may have been a mixture of several effects, including gustatory responses following the consumption of beverages like bitter lemon, which could have acted towards decreasing heart rate in some subjects (Newlin et al, 1990). To our surprise, DOAs showed the expected HR increases from sober to intoxicated baseline conditions, but lacked dampening effects under stress conditions.…”
Section: Discussionmentioning
confidence: 82%
“…Numerous investigations support the contention that acute alcohol ingestion results in a decrease of heart rate variability, which is partially mediated by brainstem centers via the vagal nerve [24,35,45,56]. For example, Weise et al [56] reported that acute alcohol (0.7 g ethanol/ kg bodyweight) decreased heart rate variability.…”
Section: Introductionmentioning
confidence: 85%
“…The significant negative correlation between RSA and the lipoproteins (LDL, CHOL, TG and VLDL) closely mirrors a risk for development of coronary artery disease due to a reduced cardiac parasympathetic modulation. Newlin et al [35] and Weise et al [56], using spectral analysis, found RSA in healthy subjects to be reduced after moderate alcohol consumption. With the time domain method, we did not find a significant decrease in RSA or a change in IBI after moderate alcohol intake, whereas RSA with acoustic stimulation did change significantly.…”
Section: Rsa With Auditory Stimulation In Healthy Subjects and The Rimentioning
confidence: 99%
See 1 more Smart Citation